The Influence of Human Resource Competence on Business Performance by Mediating Innovation Capabilities in MSMEs in Ternate City - Yuli Setyowati; Abdullah W. Jabid; Sulfi Abdul Haji (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the influence of human resource (HR) competence on business performance mediated by innovation capabilities in MSMEs in the food and beverage processing sector in Ternate City. This study uses a quantitative approach with a survey method of 176 MSME actors. The analysis method uses SEM-PLS with the help of the SmartPLS 4.0.25 application. The results of the study show that: (1) HR competence has a significant effect on MSME business performance, (2) HR competence has a significant effect on innovation capabilities, (3) innovation capabilities have a significant effect on MSME business performance, and (4) innovation capabilities are able to significantly mediate the influence of HR competencies on MSME business performance. This research identifies the main challenges faced by MSME actors, including the need to improve human resource competencies through technical trainings and strengthening innovation capabilities to improve MSME business performance. The practical implications of this research are expected that the government pays attention to indicators that can encourage the improvement of MSME business performance, including human resource competence and how to encourage MSME innovation capabilities.